Losses in water distribution networks – a bibliometric review: general aspects and optimization (Research, Society and Development, 2021)
The research carried out in the water distribution networks is of great importance, given the social, environmental and economic impacts that have occurred due to the scarcity of water resources. Therefore, any scientific effort shown in research that studies water distribution systems is of great relevance. Techniques such as mathematical modeling, computer simulation and statistical methods are widely used in order to obtain more reliable answers, whether for the identification of the current situation of the network, as well as for the prediction of scenarios, failure events, increased demand, etc. The objective of this work is to carry out a bibliometric analysis to identify the state of the art of research that addresses the theme of water distribution networks for the control and reduction of the volume of water losses, which will serve as a guide for future works to to structure itself in the most relevant researches that study the theme. The developed methodology was able to analyze a metadata composed of 4188 documents taken from the Web of Science journals database. As a result, a geographical view of the theme was obtained, pointing out the main countries, affiliations, journals and researchers, as well as pointing out the main documents and relevance of the theme. It can be concluded after the results obtained that bibliometric analysis is an important tool for obtaining the state of the art. With it is possible to have a better understanding of the current situation in the development of research, familiarizing researchers with what is most current and relevant.